Essential genes Ptgs2, Tlr4, and Ccr2 regulate neuro-inflammation during the acute phase of cerebral ischemic in mice - Hongxiang Jiang; Zhiqiang Sun; Xiwei Zhu; Fei Li; Qianxue Chen (Scientific Reports, 2023)
Abstract Ischemic stroke (IS) is associated with changes in gene expression patterns in the ischemic penumbra and extensive neurovascular inflammation. However, the key molecules related to the inflammatory response in the acute phase of IS remain unclear. To address this knowledge gap, conducted a study using Gene Set Enrichment Analysis (GSEA) on two gene expression profiles, GSE58720 and GSE202659, downloaded from the GEO database. We screened differentially expressed genes (DEGs) using GEO2R and analyzed 170 differentially expressed intersection genes for Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment and Gene Ontology (GO) analysis. We also used Metascape, DAVID, STRING, Cytoscape, and TargetScan to identify candidate miRNAs and genes. The targeted genes and miRNA molecule were clarified using the mice middle cerebral artery occlusion-reperfusion (MCAO/R) model. Our findings revealed that 170 genes were correlated with cytokine production and inflammatory cell activation, as determined by GO and KEGG analyses. Cluster analysis identified 11 hub genes highly associated with neuroinflammation: Ccl7, Tnf, Ccl4, Timp1, Ccl3, Ccr1, Sele, Ccr2, Tlr4, Ptgs2, and Il6. TargetScan results suggested that Ptgs2, Tlr4, and Ccr2 might be regulated by miR-202-3p. In the MCAO/R model, the level of miR-202-3p decreased, while the levels of Ptgs2, Tlr4, and Ccr2 increased compared to the sham group. Knockdown of miR-202-3p exacerbated ischemic reperfusion injury (IRI) through neuroinflammation both in vivo and in vitro. Our study also demonstrated that mRNA and protein levels of Ptgs2, Tlr4, and Ccr2 increased in the MCAO/R model with miR-202-3p knockdown. These findings suggest that differentially expressed genes, including Ptgs2, Tlr4, and Ccr2 may play crucial roles in the neuroinflammation of IS, and their expression may be negatively regulated by miR-202-3p. Our study provides new insights into the regulation of neuroinflammation in IS.